2001
DOI: 10.1177/0310057x0102900312
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Fibreoptic Bronchoscopy during Neonatal Tracheo-Oesophageal Fistula Ligation and Oesophageal Atresia Repair

Abstract: Maintenance of adequate ventilation under anaesthesia can be difficult during identification and ligation of congenital tracheo-oesophageal fistula with repair of oesophageal atresia. Anaesthesia may also be complicated by problems associated with prematurity, pre-existing aspiration pneumonitis, and difficulty positioning the endotracheal tube to prevent inflation of the stomach with increased risk of aspiration and diaphragmatic splinting. Even intubation of the fistula and gastric rupture may occur. Two neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…These considerations led us to use the technique of fiberoptic TARTEF with IPPV. Fiberoptic TARTEF has several advantages over TARTEF using a rigid bronchoscope: (i) it is technically easier, less invasive, provides all the information needed, helps to avoid accidental fistula intubation and is repeatable whenever required; (ii) with new ultrathin fiberscopes, repeated atraumatic bronchoscopy for the detection of the fistula and other airway anomalies through the tracheal tube is feasible even in the smallest neonates (7); (iii) fiberoptic bronchoscopy through the tracheal tube is an easy procedure, which can normally be performed by pediatric anesthetists experienced in endoscopic airway management (14); (iv) fiberoptic TARTEF can be performed in the already intubated patient and does not usually prolong anesthesia time to a significant extent; (v) assessment of tracheomalacia with a fiberbronchoscope is more reliable than with a rigid bronchoscope, which significantly counteracts the collapsing forces; (vi) interruption of the bronchoscopic procedure to resume unimpeded ventilation is always and instantly possible. This allows repeated intraoperative endoscopy for fistula transillumination by the bright light of the bronchoscope to help the surgeon quickly identify and ligate the fistula and to prevent inadvertent ligation of a main bronchus with almost absolute certainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations led us to use the technique of fiberoptic TARTEF with IPPV. Fiberoptic TARTEF has several advantages over TARTEF using a rigid bronchoscope: (i) it is technically easier, less invasive, provides all the information needed, helps to avoid accidental fistula intubation and is repeatable whenever required; (ii) with new ultrathin fiberscopes, repeated atraumatic bronchoscopy for the detection of the fistula and other airway anomalies through the tracheal tube is feasible even in the smallest neonates (7); (iii) fiberoptic bronchoscopy through the tracheal tube is an easy procedure, which can normally be performed by pediatric anesthetists experienced in endoscopic airway management (14); (iv) fiberoptic TARTEF can be performed in the already intubated patient and does not usually prolong anesthesia time to a significant extent; (v) assessment of tracheomalacia with a fiberbronchoscope is more reliable than with a rigid bronchoscope, which significantly counteracts the collapsing forces; (vi) interruption of the bronchoscopic procedure to resume unimpeded ventilation is always and instantly possible. This allows repeated intraoperative endoscopy for fistula transillumination by the bright light of the bronchoscope to help the surgeon quickly identify and ligate the fistula and to prevent inadvertent ligation of a main bronchus with almost absolute certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Fiberoptic tracheoscopy assisted repair of tracheoesophageal fistula (TARTEF) is a newer technique, providing additional information for the surgeon regarding identification of the fistula and its precise ligation during surgery (7–9).…”
Section: Introductionmentioning
confidence: 99%
“…Studies discussing anesthetic management and outcomes in this patient population largely appear prior to the 1970s (9)(10)(11)(12)(13). More recently, case reports and retrospective studies have been presented but none has directly assessed the impact of coexisting congenital heart disease on the perioperative anesthetic management and survival to hospital discharge of these patients (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…However, this results in exposure to radiation. 15 Bronchoscopy could also be used to ensure the balloon is not in the trachea or major bronchi, but though several authors have demonstrated that intraoperative bronchoscopy is useful for rapid confirmation of correct placement of endotracheal tube and to avoid accidental intubation of the TEF, 16,17 bronchoscopy in infants is technically complicated and involves essentially high-risk procedures that can result in serious complications such as hypoxia, bronchospasm, bleeding, pneumothorax, and arrhythmia. 18,19 Therefore, given the disadvantages of the latter two diagnostic approaches, the awareness of the possibility of airway obstruction appears to be the most important factor in prevention of this complication.…”
Section: Discussionmentioning
confidence: 99%